2008
DOI: 10.1097/aln.0b013e3181862a33
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine Weakens Dynamic Cerebral Autoregulation as Assessed by Transfer Function Analysis and the Thigh Cuff Method

Abstract: Contrary to the authors' hypothesis, the current results of two experimental analyses suggest together that dexmedetomidine weakens dynamic cerebral autoregulation and delays restoration in CBF velocity during conditions of decreased steady state CBF velocity. Therefore, dexmedetomidine may lead to further sustained reductions in CBF during temporal decreases in arterial pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 41 publications
1
34
1
1
Order By: Relevance
“…The increase in the vascular resistance suggests that DEX may induce peripheral vasoconstriction caused by α2B receptor-medicated mechanisms, as in cerebral vessels. However, the relative increase in vascular resistance in the oral tissues was smaller than that in cerebral vessels when compared to the report of Ogawa et al 24 , even at the same administration rate. In addition, there is no report investigating the distribution of α2B receptors in oral tissues.…”
Section: Discussioncontrasting
confidence: 41%
See 2 more Smart Citations
“…The increase in the vascular resistance suggests that DEX may induce peripheral vasoconstriction caused by α2B receptor-medicated mechanisms, as in cerebral vessels. However, the relative increase in vascular resistance in the oral tissues was smaller than that in cerebral vessels when compared to the report of Ogawa et al 24 , even at the same administration rate. In addition, there is no report investigating the distribution of α2B receptors in oral tissues.…”
Section: Discussioncontrasting
confidence: 41%
“…33-35 As described above, cerebral vessels are thought to contain many α2B receptors. Ogawa et al 24 administered DEX to volunteers either at low flow rate (3 μg・kg -1 ・hr -1 for 10 min, followed by 0.2 μg・ kg -1 ・hr -1 for 60 min), or at high flow rate (6 μg・kg -1 ・hr -1 for 10min, followed by 0.4…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, fixing a line through several singular subject MAP/CBF relationships ignores the potential of chronic resetting, e.g., in the case with sustained hypertension [7]. Upon closer examination of the response for CBF (or a related index of CBF) to a change in MAP, recent studies have revealed that this relationship appears to be more pressure passive [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] than previously described. However, the limitations to drawing inferences from the majority of recent studies are threefold.…”
Section: Introductionmentioning
confidence: 87%
“…У больных с септическим шоком дексме детомидин уменьшает чувствительность к СО 2 в большей сте пени, чем пропофол [46]. Препарат снижает эффективность ауторегуляции мозгового кровотока при колебаниях АД [47].…”
Section: о б з о р ыunclassified